Blood Groups - Tombak, Anil (IntechOpen, 2019)
Blood groups, erythrocyte antigens, and transfusion are fundamental areas of medicine and are related to many disciplines of science like hematology, immunology, surgery, and genetics. This book is a collection of information related to blood groups and transfusion, and a practical resource for all concerned physicians. The book is divided into two sections. The first section includes chapters on blood transfusion reactions and hemolytic disease of the fetus. The second section includes information for the future perspectives of blood group antigens. This book will be a stepping stone for scientists who are rapidly advancing their science journey.